Teologi Ibn ‘Arabī - Arrazy Hasyim (Himpunan Peminat Ilmu-Ilmu Ushuluddin (HIPIUS), 2012)
This article propounds a study on Ibn ‘Arabī through theological approach. The study will show that Ibn ‘Arabī is a follower of Sunnī theology. This hypothesis can be proved via genealogical structure towards Ibn ‘Arabī’s knowledge tradition which is complex, and by tracing his statements containing theological expressions within his works. Nonetheless, it cannot be denied that his several words very potentially invite criticism and being considered infidel. However, in principle, those critiques come from critics do not have spiritual background as owned by Ibn ‘Arabī. Or there had been another assumption, i.e. it is caused by ‘insertion’ from his intellectual rivals, as stated by Ibn ‘Arabī’s proponents. In fact, Ibn ‘Arabī himself asserts, “Who believes in hulūl, then his religion is defective.”